EFEKTIVITAS SENAM HAMIL TERHADAP KUALITAS TIDUR PADA IBU HAMIL TRIMESTER III - Gismaka Qoirunissa Putri; Nurry Ayuningtyas Kusumastusti (Nusantara Hasana Berdikari, 2021)
Sleep disturbance is caused by the bigger the pregnancy so that the diaphragm will be pressed upwards and interfere with breathing. Poor breathing in pregnant women will affect the decrease in oxygen to the brain so that it can affect the quality of sleep in pregnant women. At that time, pregnant women often experience anxiety due to vigilance about the emergence of signs and symptoms of childbirth which causes a decrease in the quality of sleep in pregnant women. The effort made to overcome sleep difficulties is to do the safest exercise for pregnant women is pregnant exercise. The purpose of this study was to determine the effectiveness of pregnancy exercise on sleep quality in third trimester pregnant women based on a systematic literature review. Research method: using systematic literature review by determining the inclusion and exclusion criteria using PICOS and following the flowchart diagram. Results: From the 5 journals obtained, it shows that pregnancy exercise affects the quality of sleep in the third trimester of pregnant women.